Analysis of the Composite Structure of the Cornea‐Contact Lens Assembly in Orthokeratology. Issue 1 (21st August 2022) - Bodi, Gyury; Baritz, Mihaela I.; Repanovici, Angela; Barbu, Daniela M.
Abstract: Contact lenses are currently a practical and effective solution for the correction of refractive errors but also for the application of orthokeratology procedures in cases of keratoconus or high myopia pathologies. In orthokeratology procedures, the contact lenses used are rigid (hard) and are made of biocompatible materials resulting in a composite structure together with the cornea of the human eye. Thus, the contact lenses for orthokeratology have the effect of deforming the corneal surface, in the latter inducing a series of residual and inertial stress states through which changes in the refractive power of the entire eyeball are obtained. This paper presents aspects related to the approach of the corneal‐contact lens composite structure as a thin curved plate set. Also, the study is completed with the determination of the different aspects in section and an anisotropic structure which implies an approach of biomechanical behavioral analyzes both in terms of the elastic component and the viscosity component manifested in the corneal structure. As shown by specialists, the cornea topography is determined by the balanced state between the internal and external forces acting on it and its mechanical rigidity, which is, in turn, defined by the cornea geometry, the biomaterial thickness, and rigidity. Therefore, the development of studies on the corneal‐contact lens combination in orthokeratology as a composite structure is closest to the real behavior of the whole.